Pengaruh Kesadaran Wajib Pajak, Akuntabilits Pelayanan Publik, Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Agus Wahyudi; Leonardus Yoskarlin Gadut; Hilarius Seman (Fakultas Ekonomi dan Bisnis Unram, 2026)
This research is motivated by the low realization of motor vehicle tax revenue that has not reached the target even though West Manggarai Regency is a super priority tourism destination with continuously increasing infrastructure development. This study aims to examine the effect of taxpayer awareness, public service accountability, and tax sanctions on motor vehicle taxpayer compliance in West Manggarai Regency. The study uses a quantitative approach with an associative method. The respondents were 100 motor vehicle taxpayers registered at the West Manggarai Regency SAMSAT Office. The data collection technique was carried out through the distribution of questionnaires and analyzed using multiple linear regression. The results of the study indicate that taxpayer awareness and tax sanctions influence motor vehicle taxpayer compliance. Meanwhile, public service accountability does not affect taxpayer compliance. This study contributes as evaluation material for local governments in improving taxpayer compliance through increasing tax awareness and implementing strict sanctions to optimize regional revenue.